5:20:20:5 EFFICIENCY - Chang, Shengmei; Zhu, Nan (PUPIL: International Journal of Teaching, Education and Learning, 2018)
Some researchers claim that the typical student’s attention span is about 10 to 15 minutes, but most classes last 50 to 90 minutes. In addition, some educators argue that technology can distract students more than it can help them, which makes it harder for teachers to capture student’s attention while teaching them. How a language teacher captures students’ attention and efficiently utilizes the entire 50 minutes is a challenge. The goals of this presentation are to demonstrate how to make the best use of the 50 minutes and to show how technology can be applied to get students engaged.The 50 minutes are divided into 4 phases: 5:20:20:5. The first 5 minutes aims to warm up students’ background knowledge or review related materials. The first 20 minutes focuses on leading students into the core materials for that learning period. The following 20 minutes centers on assessing what students have or have not learned in the previous 20 minutes. The last 5 minutes summarizes the core materials and clarifies any questions. Within each learning period, teachers can use visual and audio applications, such as Power Point slides, Kahoot games, SMART Board and Linoit.com activities, to keep students interested and motivated and make both teaching and learning fun.